Hubungan Status Gizi Balita Dengan Kejadian Infeksi Di Kecamatan Getasan - Franzesca Dwi Wahyu; R L N K Retno Triandhini; Sharon Regina Yalmav (Jurnal Keperawatan Muhammadiyah, 2020)
Abstract                                                       Background: In developing countries, infant and child mortality rates are relatively higher compared to developed countries. The main causes of death are infectious and parasitic diseases, and many of them are associated with malnutrition. Infectious diseases are closely related to poor nutritional status. Purpose: to analyze the relationship between nutritional status of children with the incidence of infection in Getasan and see the factors that influence the incidence of infection. Methods: This type of quantitative research is cross sectional to study the relationship of nutritional status with the incidence of infection in Getasan. To find the relationship between nutritional status and infection using 2 methods, namely using descriptive analysis or univariate and bivariate using Spearmen R'ho Correlation Test. Results: Obtained a correlation coefficient (r) = 0.056 (α = <0.05). This shows that there is no correlation between toddler nutrition status and infectious events in Tolokan village. Discussion: Nutritional status is not only affected by infection in infants but also caused by several factors including genetic, psychological, social status, education, household income and the environment. Conclusion: Nutritional status in the village is caused by various factors, namely hand washing habits, smoking habits, the absence of chimneys and the presence of pets at home.Keywords: nutritional status, infection, infant.